THE DEVELOPMENT OF SOME BASIC PRINCIPLES OF ANTI-CRIMINAL PROCEEDINGS OF UKRAINE - Lantsedova, Yulia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article presents the development of a new doctrine of the person concerned and a neutral sentence. Designed by S. Kirichenko and by A. Tuntula and basically developed by the author the doctrine of the person concerned and a neutral judgment is based on the fact that the concept of legal certainty applies to all subjects of the anti-criminal proceedings and, above all, to the persecuted and to the victim (the plaintiff). Any, and especially the final procedural decision on the anti-criminal proceedings shall be made in a coherent and sufficient weight of evidence that each individual evidence must also have the unity of the main basis of legal properties (their relevance, legitimacy, acceptability, purity, authenticity). And as a result of a proper assessment of coherent and sufficient set of this kind of evidence the judge will develop the inner conviction of the guilt of a person –the indictment shall be passed, and if the innocence of the person –the acquittal shall be passed. Particular attention is paid to the possibilities of improving the professionalism of the new doctrine of the anticriminal and other types of antidelictual proceedings. Like any other type of anti-delictualproceedings the anti-criminal proceedings should be carried out only on a professional basis, that is only by professionals, who have mastered by stationary high school training centuries of experience, knowledge and skills to carry out such acts, and the appropriate level of analytical thinking, and are required to provide a direct, objective, comprehensive and complete investigation of all the circumstances of the case, on this basis to establish the objective truth and to resolve correctly anti-criminal or otherwise anti-delictual case. Considered in detail are the provisions of the new doctrine of establishing objective truth in anantidelictual case.